The Influence of Monetary and Non Monetary Reward on Desired Employee Outcome Among Nurses at Hospital in Kuantan - Muhammad Salehuddin, Ismail (2023)
This paper aims at analysing the influence of monetary and non-monetary rewards on desired employee outcomes. The research objective attempts to provide relationship between monetary rewards and non-monetary rewards towards desired employee outcomes as well as enhancing the validity and reliability of the existing research. This study is using quantitative data in order through collecting online questionnaires to analyze influence of monetary rewards and non-monetary rewards towards employee productivity, employee turnover and employee engagement containing a time lag of three months among nurses at Hospital in Kuantan. Realibility analysis, correlation analysis, deccriptive analysis and multiple regression analysis was used to measure the outcome between monetary rewards and non-monetary rewards towards desired employee outcomes. The results of the study reveal a positive relationship between the employee engagement and the independent variables which are monetary rewards and non-monetary rewards while the results rejected the influence of monetary rewards and non-monetary rewards towards employee productivity and employee engagement.